Rekonstruksi Maqasid Al-Syariah dalam Pemikiran Hukum Islam Kontemporer: (Upaya Mewujudkan Keadilan Bagi Perempuan di Era Modern) - Nurwihda Ramadani; Sakina Sakina; Putri Abelia Z; Kurniati Kurniati (International Forum of Researchers and Lecturers, 2025)
Injustice against women in contemporary Islamic law practice is still a serious problem, especially in cases of divorce, child custody, and the division of common property, which are often decided textually without considering the social, economic, and psychological aspects of women. This phenomenon shows that the application of Islamic law is still normative and does not fully reflect substantive justice as the purpose of maqāṣid al-syarī'ah. This research aims to analyze the nature of justice for women in the modern era, identify the steps needed to realize this justice, and formulate Islamic legal solutions based on maqāṣid al-syarī'ah that can be applied contextually in the religious justice system. The research method used is qualitative with a normative-empirical approach through literature analysis, case studies, and empirical data from religious court decisions and reports of official institutions such as Komnas Perempuan. The results of the study show that justice for women can only be achieved through a dynamic maqāṣid approach, by placing the interests of women and children above the legal-formalities of classical fiqh. The efforts needed include the integration of empirical data in judges' decisions, reform of religious justice policies, increasing the capacity of judges in understanding maqāṣid, and empowering women through legal literacy.